Sleeve gastrectomy - still popular bariatric method - Kasalický, M; Koblihová, E; Pohnán, R (Rozhledy v chirurgii, 2024)
INTRODUCTION: Obesity is currently the most common multifactorial disease affecting almost all social strata of the population. Conservative therapy of obesity usually succeeds in reducing excess weight by an average of 10-15%. After surgical treatment of severe obesity (bariatric surgery), the average decrease in excess weight is several times greater and, in most cases, has a long-term positive effect on the overall clinical condition of the patients. METHODS: Sleeve gastrectomy (SG) is the most used bariatric method of treating severe obesity today. The principle of SG is a vertical resection of a major portion of the gastric greater curvature. After the resection, the residual stomach has the shape of a sleeve with a remaining volume of about 120-150 ml. The effect of the method is both restrictive and hormonal, because after SG, the plasma level of active ghrelin decreases in the long term, among other things. CONCLUSION: Obesity is considered one of the most serious global health problems today. In 2018 a total of 696,191 bariatric procedures were performed worldwide. Sleeve gastrectomy was originally used in high-risk severely obese patients as the first stage of a duodenal switch (DS) or gastric bypass. Since 2003, this method has been used independently because for most of the patients, SG had a sufficient effect on weight reduction and improvement of comorbidities, and that is why since 2015, SG has become the most frequently used bariatric method.
Keywords: Gastrectomy; Obesity; Retrospective Studies; lidé; výsledek terapie; Laparoscopy; gastrektomie; žaludeční bypass; bariatrická chirurgie; Gastric Bypass; retrospektivní studie; Humans; bariatric surgery; sleeve gastrectomy; obezita; Bariatric Surgery; laparoskopie; severe obesity; Treatment Outcome; Obesity, Morbid; morbidní obezita